Arabic Phoneme Learning Challenges for Madurese Students and the Solutions - Fudhaili, Achmad; Edidarmo, Toto; Maisaroh, Siti (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2023)
This article discussed the challenges in pronouncing Arabic phonemes by students at INSTIKA Madura. Phoneme pronunciation is the most important principle in Arabic. Without the correct phoneme pronunciation, a language cannot be understood. The problem of phoneme pronunciation was investigated and a solution was found based on factor analysis. Qualitative descriptive research design was used with a case study approach. Data collection methods include interviews with lecturers and students, direct observation of in-class learning and documentation of the results of lecturer notes. The data analysis model adhered the interactive model of Miles, Huberman, and Saldana. Validity was ensured through passion, observation, triangulation, and expert views. The finding of the research showed problems with Arabic phonemes, which were categorized as Akhtha’ al-Harakat, Akhtha’ al-Ibdal, Akhtha’ al-Hadzf, and Akhtha’ al-Tahrif. Factors include language problems (characteristics of the first and second languages) and non-language problems (student characteristics, lecturer competence, learning strategies, lesson materials, and learning facilities). The proposed solutions included error and comparative analysis for language problems, motivation, diagnosis, cooperative learning, detailed examples, pronunciation exercises, and adequate facilities for non-language problems. This research provided a comprehensive study of the challenges of pronouncing Arabic phonemes at INSTIKA Madura. Certain types of errors and the underlying factors that affect pronunciation were identified. Practical solutions were proposed, addressing both language and non-language aspects to improve students' pronunciation skills. These findings offered valuable insights for educators, curriculum developers and language instructors, facilitating targeted interventions and effective teaching strategies to students struggling with Arabic phonetics.